Sirih Pinang as a Cultural Path to Forgiveness in the Arab-Malay Community of Jambi - Rion Nofrianda; Agung Iranda; Fadzlul Fadzlul; Francisca Francisca; M. Fikri Dzacky Akbar; Melsa Firnanda; Nadia Nadia; Nur Maidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study explores the meaning of forgiveness within the sirih pinang tradition as a cultural mechanism for conflict resolution in the Arab-Malay community of Seberang, Jambi City. Using a qualitative phenomenological method, the research examines the lived experiences of a traditional leader and a family member of a conflict perpetrator. Data were gathered through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). Findings reveal nine key themes, including symbolic meanings, ritual functions, stages of reconciliation, and the interplay between customary and formal law. The tradition emphasizes sincerity, moral responsibility, and mutual agreement, expressed through cultural symbols such as white cloth and ritual offerings. However, this study is limited by the small number of participants and its focus on a specific cultural setting, which may affect the transferability of the findings to other communities or conflict contexts. Despite these limitations, the study highlights sirih pinang as a culturally embedded form of forgiveness both social and spiritual rooted in local wisdom and communal values.